Persepsi Masyarakat terhadap Kebijakan Hukuman Mati dalam Kasus Narkotika di Indonesia: Analisis Kuantitatif melalui Survei Nasional - Idris, Maulana Fahmi; Laksito, Joni (Hakim: Jurnal Ilmu Hukum dan Sosial, 2024)
The death penalty remains one of the most contentious policies in addressing narcotics crimes in Indonesia. While implemented as a stringent measure to combat drug trafficking, the policy often sparks debates regarding its effectiveness and implications for human rights. This study aims to analyze public perceptions of the death penalty policy for narcotics-related offenses, focusing on how demographic factors such as age, education, and residence influence public support. Using a quantitative approach, this research employed a nationwide survey involving 1,500 respondents selected through stratified random sampling. Data collection combined online and offline methods to ensure broad representation. The findings reveal significant demographic variations in support for the death penalty. Younger and middle-aged respondents (25–40 years old) showed the highest levels of support (70%), particularly in urban areas (70%) compared to rural areas (55%). Educational attainment also influenced perspectives, with higher education levels correlating with increased support for the policy. The study concludes that public perceptions of the death penalty are shaped significantly by demographic and socio-cultural factors. These findings underscore the need for targeted communication strategies to address varying public concerns, particularly in rural areas where access to information may be limited. The research contributes to policy discussions by providing empirical insights into public opinion on this controversial issue. It recommends integrating public education campaigns and alternative rehabilitative measures to enhance public understanding and acceptance of narcotics policies. By grounding policy development in evidence-based research, this study aims to support more equitable and effective approaches to addressing drug-related crimes in Indonesia